2019
DOI: 10.1007/s00268-019-05181-x
|View full text |Cite
|
Sign up to set email alerts
|

The Combined SIRS + qSOFA (qSIRS) Score is More Accurate Than qSOFA Alone in Predicting Mortality in Patients with Surgical Sepsis in an LMIC Emergency Department

Abstract: Background qSOFA has been proposed as a prognostic tool in patients with sepsis. This study set out to assess the sensitivity of several scores, namely: the pre‐ICU qSOFA, the qSOFA with lactate (qSOFA L), SIRS score, qSOFA + SIRS score (qSIRS) and qSIRS with lactate (qSIRS L) in predicting in‐hospital mortality in patients with surgical sepsis as well as the sensitivity of these scores in predicting high‐grade sepsis. The secondary aim was to determine which of these scores is best suited to predict high‐grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 59 publications
0
22
0
1
Order By: Relevance
“…While substantial research has been performed in the use of risk stratification tools to guide activation and appropriate destinations for patients with trauma (3)(4)(5), stroke (6)(7)(8)(9), or sepsis (10,11), there have been limited efforts to approximate risk and inform treatment and destination decisions for the broader EMS patient population. The Modified Early Warning Score (MEWS) (12) and the National Early Warning Score (NEWS) (13) have shown prognostic value in the prehospital setting as predictors of hospital mortality (14,15).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…While substantial research has been performed in the use of risk stratification tools to guide activation and appropriate destinations for patients with trauma (3)(4)(5), stroke (6)(7)(8)(9), or sepsis (10,11), there have been limited efforts to approximate risk and inform treatment and destination decisions for the broader EMS patient population. The Modified Early Warning Score (MEWS) (12) and the National Early Warning Score (NEWS) (13) have shown prognostic value in the prehospital setting as predictors of hospital mortality (14,15).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The median initial prehospital REMS was lower among patients who survived to discharge (5, [IQR: 3-8]) compared to those who did not survive to discharge (9, [IQR: [6][7][8][9][10][11][12]). All patients with an initial prehospital REMS of 0 (11%) survived to discharge.…”
Section: Rems As a Predictor Of Overall Survival To Dischargementioning
confidence: 99%
“…In contrast, studies also demonstrated similar prognostic performances regardless of the choice of qSOFA or SIRS [5,6]. Recently a retrospective study demonstrated that combined qSOFA and SIRS are more accurate than qSOFA alone in predicting in-hospital mortality in patients with surgical sepsis [7]. In our systematic review of 45 studies with 431,634 patients, we showed that qSOFA for in-hospital mortality in all patients (with or without suspected infection) was poor [8].…”
Section: Introductionmentioning
confidence: 63%
“…Studies of infected patients have also been in agreement with our findings. In a retrospective study of patients with surgical sepsis, the combination of qSOFA þ SIRS (qSIRS) was more accurate than qSOFA alone in predicting mortality [7]. Other groups have demonstrated that NEWS and modified early warning score (MEWS) are more accurate than qSOFA for predicting poor outcomes for infected patients [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation